Depression, anxiety and stress levels in a Mexican sample during confinement by COVID-19 - Teresa Aspera-Campos; Rodrigo César León-Hernández; Roandy Gaspar Hernandez-Carranco (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2021)
Social confinement by COVID-19 affects mental health. Therefore, the objectives were: 1) to determine the levels of depression, anxiety and stress during the confinement by strata 2) to analyze the changes before and during the confinement, and 3) to identify the factors that increase the risk for said emotional states. Ex post facto study with repeated measures and explanatory in 768 subjects, both sexes, from different entities of the Mexican Repu-blic. Non-probability sampling (snowball) was used, using an electronic survey with sociodemo-graphic data and the DASS-21 scale with adapted response options. During confinement, depression (t = -15.41, p <.001) and anxiety (t = -5.55, p <.001) increased, except stress (t = -1.10, p = .271). The regression models adjusted for the three dependent variables (p > .05), the risk factors were gen-der, not having a safe salary, having children, being married and younger. It is concluded that affective levels increased during confinement and the models agree that female sex is a common risk factor among depression, anxiety and stress during the pandemic